The Kookies Monstr / Wan Nur Jannah Wan Mohamad Zuki - Wan Mohamad Zuki, Wan Nur Jannah (2021)
Social media is a platform and application that allows users to produce and share information as well as participate in social networking. The majority of the people use especially on a regular basis, including Facebook, Instagram, Twitter, Whatsapp, and others. People can easily obtain information through social media, therefore this is a great opportunity for an entrepreneur to make their product known to the general public. In this project, we would want to discuss how the business is growing and how we advertise our product on social media to make it known to the general public. Soft sale, hard sell, and teaser are some of the tactics used to attract people to purchase our products. As we all know, technology and social media are the focus of today's world. As a result, by utilising a platform such as the application of Facebook, it will be easier to increase brand recognition. The Kookies Monstr is a business that sells viral products nowadays because Malaysian’s people love to eat something when it went viral. Many people love to watch movie at the cinema and buy this product as their companion while enjoying their movie time moment. Also, students currently doing an assignment at their home and always feel hungry during late night but our product can give them something easy to eat. Thus, because of that, many people start a cookies business to fulfil the demand. We understand that some cookies sell in the market nowadays is not as good and because of that, The Kookies Monstr finds the solution and create a good recipe in cookies making to make it as the best among other competitors. Also, The Kookies Monstr also produces brownies product that taste so unique makes the customers to repeat to buy again. Our products can be eaten by everyone especially kids, teenagers, and even students. Our business is located in the Subang Jaya but we are selling online in the Facebook so it is easy to sell our product and find customer. The Kookies Monstr will deliver the highest quality items to meet the needs of its consumers.